The efficacy of fractional CO2 laser in acne scar treatment: A meta‐analysis - Zhang, Ding‐Ding; Zhao, Wan‐Yi; Fang, Qing‐Qing; Wang, Zheng‐Cai; Wang, Xiao‐Feng; Zhang, Min‐Xia; Hu, Yan‐Yan; Zheng, Bin; Tan, Wei‐Qiang (Dermatologic therapy, 2021)
Fractional CO2 laser is a good option for treating acne scars. However, the clinical efficacy of this treatment modality requires further evidence. To perform a meta‐analysis to assess clinical improvements in acne scars with fractional CO2 laser and non‐CO2 laser therapies. Databases (PubMed, Embase, Cochrane Library) were searched using the search strategy to identify eligible studies. All statistical analyses were performed using the Review Manager 5.0, and a meta‐analysis was conducted to assess the effects of fractional CO2 laser used as a treatment for acne scars. Eight studies were included for further analysis. There was no significant difference between fractional CO2 laser and non‐CO2 laser therapies in terms of clinical improvement, observer assessment (P = .19), patient assessment (P = .91), and incidence of post‐inflammatory hyperpigmentation (P = .69). The subgroup analyses showed that the duration of follow‐up had little effect on the evaluation of treatment effect. The efficacy of fractional CO2 laser therapy in acne scars appeared to be equal to that of non‐CO2 laser therapies. More well designed randomized controlled trials and more credible and standard evaluation criteria are needed, and the efficiency of combination therapy requires further analysis.